2022
DOI: 10.3389/fmars.2021.774041
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and Biodiversity of the Intertidal Barnacle Tetraclita Species in the Gulf of Thailand and Andaman Sea – Influences of Oceanographic Currents and Pleistocene Glaciations

Abstract: The present study investigated the phylogeography of the intertidal barnacle Tetraclita in the Gulf of Thailand ecoregion (Sunda Shelf Province in the Pacific) and the Andaman Sea Coral Coast ecoregion (Andaman Province in the Indian Ocean) in Thailand’s waters. Tetraclita species were identified by a combined morphological and molecular approach using mitochondrial gene fragments (CO1 and 12S rRNA). Tetraclita singaporensis is a major occupiers on the Andaman coast but is sparse in the western Gulf of Thailan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Acorn barnacles are sessile crustaceans that permanently attach to biotic (e.g., turtles, whales, and coral) and abiotic surfaces (e.g., rocky shores), especially in intertidal zones. In Thailand, three major families of Cirripedia (Thoracica) have been identified: Balanidae, Tetraclitidae, and Chthamalidae (Chan et al, 2022; Pochai et al, 2017; Sukparangsi et al, 2019). Amphibalanus amphitrite ( Darwin 1854) is a balanid barnacle with a wide distribution range in the Gulf of Thailand and the Andaman Sea (Pochai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Acorn barnacles are sessile crustaceans that permanently attach to biotic (e.g., turtles, whales, and coral) and abiotic surfaces (e.g., rocky shores), especially in intertidal zones. In Thailand, three major families of Cirripedia (Thoracica) have been identified: Balanidae, Tetraclitidae, and Chthamalidae (Chan et al, 2022; Pochai et al, 2017; Sukparangsi et al, 2019). Amphibalanus amphitrite ( Darwin 1854) is a balanid barnacle with a wide distribution range in the Gulf of Thailand and the Andaman Sea (Pochai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Geographical differentiation is common for marine species due to historical events (Palumbi, 1994;Wang et al, 2015), oceanographic forces (Chan et al, 2022;Dong et al, 2012;Li, Dai, et al, 2021), habitat discontinuity (Wort et al, 2019), dispersal ability (Cowen & Sponaugle, 2009), and water temperature (Cheng & Sha, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Geographical differentiation is common for marine species due to historical events (Palumbi, 1994 ; Wang et al, 2015 ), oceanographic forces (Chan et al, 2022 ; Dong et al, 2012 ; Li, Dai, et al, 2021 ), habitat discontinuity (Wort et al, 2019 ), dispersal ability (Cowen & Sponaugle, 2009 ), and water temperature (Cheng & Sha, 2017 ). In the open sea, environmental gradients play an important role in genetic divergence (Hudson et al, 2017 ); for example, large‐scale temperature heterogeneity can lead to local adaptation and genetic differences (Saeedi et al, 2019 ; Sasaki & Dam, 2019 ), implying that genetic divergence at depth gradients contains important information for the understanding of phylogenetic relationships and evolutionary history (Behrens et al, 2021 ; Stefánsson et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the large geographic spatial scale, larval delivery is an important determinant of variation in recruitment. Upwelling offshore flows can transport larvae seaward and reduce the larval supply to intertidal communities (Connolly et al, 2001 ; Pfaff et al, 2011 ) but wind-driven currents can also play a key role in the dispersal of larvae shoreward (Lagos et al, 2008 ; Neo et al, 2013 ; Mazzuco et al, 2015 ; Chan et al, 2022 ) and settlements of intertidal species are enhanced by onshore winds (e.g., Bertness et al, 1996 ; Mazzuco et al, 2015 ). Moreover, high larval production has been associated with higher primary productivity in the nearshore ocean (Leslie et al, 2005 ), which can be the result of upwelling and monsoonal forcing (Liu et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are fewer large-scale storms or cyclonic activities in the Strait of Malacca Shelf province as it is more sheltered by Sumatra Island, and winds are moderate in both monsoon seasons (Brewer et al, 2015 ). Chan et al ( 2022 ) suggested that the monsoon-driven currents can affect the larval supply and diversity of barnacle species in these regions. Nonetheless, the influence of monsoon-driven oceanographic variability on the reproduction of coastal marine species is poorly understood and the west coast of Thailand is a suitable trackable model system to evaluate such effects.…”
Section: Introductionmentioning
confidence: 99%